Key parameters for droplet evaporation and mixing at the cloud edge. (2nd May 2021) - Fries, J.; Sardina, G.; Svensson, G.; Mehlig, B.
Abstract: The distribution of liquid water in ice‐free clouds determines their radiative properties, a significant source of uncertainty in weather and climate models. Evaporation and turbulent mixing cause a cloud to display large variations in droplet number density, but quite small variations in droplet size (Beals et al., Science, 2015, vol. 350, pp. 87–90). However, direct numerical simulations of the joint effect of evaporation and mixing near the cloud edge predict quite different behaviours, and how to reconcile these results with the experimental findings remains an open question. To infer the history of mixing and evaporation from observational snapshots of droplets in clouds is challenging, because clouds are transient systems. We formulated a statistical model that provides a reliable description of the evaporation–mixing process as seen in direct numerical simulations and allows us to infer important aspects of the history of observed droplet populations, highlighting the key mechanisms at work and explaining the differences between observations and simulations. Abstract : At the cloud edge, the droplet size distribution suffers rapid changes because turbulent mixing induces droplet evaporation. It is a formidable challenge to model these effects, because they involve spatial scales from microns to kilometres. We identify the key parameters of this turbulent mixing‐evaporation process from first principles by deriving a statistical model. It provides a unifying framework explaining earlier numerical‐simulation results, as well as the most detailed in‐situ observations of cloud droplets.